2008
DOI: 10.1089/scd.2008.0012
|View full text |Cite
|
Sign up to set email alerts
|

Human Dental Pulp Stem Cells Differentiate into Neural Crest-Derived Melanocytes and Have Label-Retaining and Sphere-Forming Abilities

Abstract: Adult tissues contain highly proliferative, clonogenic cells that meet criteria of multipotent stem cells and are potential sources for autologous reparative and reconstructive medicine. We demonstrated that human dental pulp contains self renewing human dental pulp stem cells (hDPSCs) capable of differentiating into mesenchymal-derived odontoblasts, osteoblasts, adipocytes, and chondrocytes and striated muscle, and interestingly, also into non-mesenchymal melanocytes. Furthermore, we showed that hDPSC culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
103
0
12

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 147 publications
(121 citation statements)
references
References 38 publications
5
103
0
12
Order By: Relevance
“…The primary DPC cultures used in our experiments expressed 86.4% -6.02 and 81.03% -8.11 of CD166 and CD105 DPSC markers, respectively, but consistent with our previous study [13], only a very few cells expressed CD271 (0.23 -0.2) and CD57 (1.39 -1.5) neural crest stem cell markers. Since the expression of surface markers is condition dependent, we did not relay on them in defining SCs and used a vital DiI dyebased functional assay to distinguish quiescent LRCs from the cycling population.…”
Section: Igf-1r and P38 Mapk Inhibitors Decrease The Pool Of Quiescensupporting
confidence: 92%
See 4 more Smart Citations
“…The primary DPC cultures used in our experiments expressed 86.4% -6.02 and 81.03% -8.11 of CD166 and CD105 DPSC markers, respectively, but consistent with our previous study [13], only a very few cells expressed CD271 (0.23 -0.2) and CD57 (1.39 -1.5) neural crest stem cell markers. Since the expression of surface markers is condition dependent, we did not relay on them in defining SCs and used a vital DiI dyebased functional assay to distinguish quiescent LRCs from the cycling population.…”
Section: Igf-1r and P38 Mapk Inhibitors Decrease The Pool Of Quiescensupporting
confidence: 92%
“…First reported in 2000 [8], the existence of DPSCs has been confirmed by many laboratories, including ours [13]; however, the exact area of the dental pulp in which they are located is still not well established. A recent study by Martens et al [14] confirmed earlier findings [4,12,15,16] that DPSCs occupy the prevascular niche and, in developing teeth, the cervical niche located near the cementum/dentin zone.…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations